Jörg Tremmel/Antony Mason/Petter Haakenstad Godli/Igor Dimitrijoski (eds.): Youth Quotas and other Efficient Forms of Youth Participation in Ageing Societies - Lena Sommerfeld (Intergenerational Justice Review, 2015)
No abstract